The antifungal potential of syzygium samarangense (Makopa) crude seed extract against candida albicans. - McGinnis, Anne Kathleen G. (2010)
This is a research study on the antifungal potential of Syzygium samarangense (Makopa) crude seed extract undertaken to determine its effect against Candida albicans. The extraction of Syzygium samarangense seeds was performed using ethanolic extraction. Different concentrations were prepared by diluting the extract with sterile distilled water to provide a 25%, 50%, and 75% concentration. It was then tested against Candida albicans using the Disk Diffusion Method (Kirby-Bauer). The study shows that Syzygium samarangense do not have any antifungal effect on Candida albicans due to the absence of a “clearing” around the disks impregnated with Syzygium samarangense extract. Therefore, the researchers conclude that the test isolates used are resistant to the phytochemical components of Syzygium samarangense. Ineffectiveness of the crude extract is attributed to some possible factors such as the strain of the test fungus used, the concentration of the extract, which may not have the antifungal components, or the concentration may be too minimal for it to be effective against the growth of the Candida albicans.